2009
DOI: 10.1002/pssc.200982551
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of photoconductivity and mobility in TlBr

Abstract: We have investigated photoconductivity and mobility in TlBr from –30 ΩC up to +20 ΩC, where the ionic conductivity is pronounced. Mobility‐related conductivity maximum superimposed on an interband‐generation conductivity growth was observed. It could be caused by the recharge of the scattering centre at about 1.65 eV. From spectral dependencies defect‐related transitions at 0.55; 0.83, 1.1; 1.32 and 1.65 eV were identified, being dependent on sample prehistory, i.e., its excitation by light and/or voltage. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In these publications, temperature dependence of the hole Hall mobility was measured. Peak values of about cm Vs [5] or cm Vs [6] below room temperature were reported as a consequence of recharging of the defects. This implies that ionized impurity scattering has a dominant role in the transport of this material.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In these publications, temperature dependence of the hole Hall mobility was measured. Peak values of about cm Vs [5] or cm Vs [6] below room temperature were reported as a consequence of recharging of the defects. This implies that ionized impurity scattering has a dominant role in the transport of this material.…”
Section: Introductionmentioning
confidence: 98%
“…In relation to the development of detectors, ionic conduction of the material has been investigated as a cause of instability in the detector's performance [5], [6]. In these publications, temperature dependence of the hole Hall mobility was measured.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, various techniques have been employed to characterize the crystalline structure, including electron backscattered diffraction and positron annihilation. (2) Also, the dynamics and transport properties of electron-hole pairs in TlBr crystals have been characterized using photoconductivity, (3)(4)(5)(6)(7)(8) photoluminescence, (9)(10)(11) cathodoluminescence, (12) and X-ray-induced radioluminescence. (10,13) We have recently applied pump-probe-type transient absorption spectroscopy to elucidate the dynamics of the electron-hole pairs produced by pulsed electron beams (14) we discussed the origin of the transient absorption and some of the dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…(8) Photoconductivity studies have revealed the transport properties of the optically produced electron-hole pairs. (9)(10)(11)(12) Similarly, photoluminescence, cathodoluminescence, and scintillation spectroscopies with steady-state and time-resolved measurements at different temperatures have revealed lattice imperfections such as point defects and dislocations. (13)(14)(15)(16) In this study, we employed transient absorption spectroscopy to characterize TlBr crystals.…”
Section: Introductionmentioning
confidence: 99%